Analisis Framing Berita Pro Kontra Proyek PSEL Pemerintah Kota Makassar di Media Tribunmakassar.com dan Fajar.co.id - Saldy Irawan; Andi Alimuddin Unde; Muliadi Mau (Jurnal Penelitian Sosial Ilmu Komunikasi, 2024)
The Makassar City Government's Waste Processing for Electrical Energy (PSEL) project has become a topic of discussion and debate in various media outlets, including Tribunmakassar.com and Fajar.co.id. These two media outlets present different perspectives in their coverage of the project. This research employs a qualitative framing analysis approach to examine the pros and cons of the two media's reporting perspectives. The primary data, in the form of several related news articles, were analyzed using Robert N. Entman's framing tools. The results of the research are distributed into the following analysis units: define problem, diagnose causes, treatment recommendation, and make moral judgment. In the Tribunmakassar.com media, the problem is defined as the rejection of residents, which is perceived as potentially detrimental to the interests of the PSEL national strategic project. Fajar.co.id presents PSEL as a solution to environmental problems and residents' land, emphasizing the justice of land payments that have not been paid for 31 years. Tribunmakassar.com's diagnosis of causes highlights the alleged existence of individuals who sought to sabotage the project or bidders who provoked the community to refuse. Fajar.co.id highlights the divergence of opinions between the municipal government and residents regarding the project's location and the potential social and financial implications. Tribunmakassar.com assesses the residents' rejection of the project as a potentially detrimental action to the interests of the PSEL project, which is a national strategic project. Fajar.co.id evaluated PSEL as a potential solution to the environmental and land issues facing residents, with a particular focus on the fairness of land payments that have been outstanding for 31 years. Tribunmakassar.com proposed the necessity for enhanced coordination, the involvement of the KPK, and the preparation of tenders as a means of overcoming differences in opinion and the intricacies of regulations. Fajar.co.id proposed that further study, transparency, and the consideration of alternative approaches could be beneficial in addressing concerns and resolving disagreements.